آلودہ اور نجس پانی کے استعمال سے متعلق شرعی نقطۂ نظر: پاکستان کے آبی بحران کے تناظر میں ایک مطالعہSharīʻah Perspectives on the use of Contaminated and Impure Water: A Study in the Context of Pakistan's Water Crisis (Al-Qamar, 2023)
This investigation aims at to discuss the polluted and Najas water usage according to the teachings of Islam. As Pakistan and the whole world is facing acute water scarcity so the reuse of water has become important phenomena in recent times. Almost all the countries are consuming polluted water after cleaning them in different treatment plants, but this aspect is neglected in Muslim countries. Although, some Muslim countries had constructed some treatment plants in their main conurbations, but the treatment of the whole wastewater is a herculean task.  This situation demands that the Najas water must be used for different needs of daily life. Islam prohibits to use the Najas water for prayers, drinking and some other needs. But it can be used in some other necessities as well. This article exposes this feature of Islamic teachings and provides answers to many questions which are related to this part. Moreover, this article suggests some appropriate uses of Najas water according to the teachings of Islam. By using Najas water, Pakistan can lessen the extent of gravity of water scarcity. As, clean water can be saved and used in other vital requirements.
Keywords: Contaminated water; Pakistan; Water-crisis, Jurists; Islam; viewpoints